The molecular basis of Clostridium difficile disease and host response. Issue 1 (January 2015) - El Feghaly, Rana E.; Bangar, Hansraj; Haslam, David B.
<x xml:space="preserve">Abstract</x> Purpose of review Clostridium difficile infection (CDI) ranges from asymptomatic colonization to severe colitis and death. The physiologic and molecular mechanisms determining disease outcome are thus far poorly understood. Here, we review recent advances in the relationship between host response to infection and disease outcome. Furthermore, we review recent studies on the relationship between intestinal microbial ecology and pathogenesis of CDI. Recent findings Severe CDI is characterized by toxin-induced epithelial injury and marked intestinal inflammation. Recent studies demonstrate that systemic markers of inflammation correlate with disease outcome. Peripheral neutrophil count, C-reactive protein, and proinflammatory cytokines are elevated in patients with severe disease as compared with asymptomatic controls. Furthermore, fecal inflammatory biomarkers are better predictors of disease severity and diarrhea persistence than C. difficile abundance. A landmark study reported higher than 80% success rate of fecal microbiota transplantation for treatment of recurrent CDI. The commensal microbes responsible for C. difficile protection, and the molecular basis by which microbial ecology impacts disease outcome, are under active investigation. Summary Under conditions of altered microbial ecology, C. difficile incites epithelial injury and marked intestinal inflammation, the primary determinant of disease outcome. Restoration of a diverse intestinal microbial population by fecal microbiota transplantation attenuates disease and prevents recurrence by mechanisms that are yet to be fully elucidated.